Economic Impact of Exergy Efficient Building Block Design - MERT, Yelda; SAYGIN, Nicel; MERT, Suha Orçun (International Journal of Contemporary Economics and Administrative Sciences, 2017)
Even after the end of 20th century, the details of connection between energy –especially energy production- and the environment were not fully understood. The population growth in last thirty years, undeniable climate changes and the starvation of non-renewable energy source reserves leaves no room for doubt, however: energy and environment share a strong and significant connection. This perspective is especially important in the world of economics, considering the cost of energy for end users. This study covers the economic impact and gain of applying exergy efficient planning to a building block. The study hereby undertakes a case study to show that an efficient planning can help save energy, and thus money. The existing blocks of the chosen case had 2% energy efficiency, while the designs proposed in the study have 10-11%. The findings in this study show that an 8 % improvement in the exergy efficiency of the building block results in 780.05TL saving for a single housing. This sums up to 54.603,49TL for the building block annually.